2011
DOI: 10.1021/ac102901e
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurements on CD24-Mediated Rolling of Human Breast Cancer MCF-7 Cells on E-Selectin

Abstract: Tumor cell rolling on the endothelium plays a key role in the initial steps of cancer metastasis, i.e. extravasation of circulating tumor cells (CTCs). Identification of the ligands that induce the rolling of cells is thus critical to understand how cancers metastasize. We have previously demonstrated that MCF-7 cells, human breast cancer cells, exhibit the rolling response selectively on E-selectinimmobilized surfaces. However, the ligand that induces rolling of MCF-7 cells on E-selectin has not yet been iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 52 publications
1
59
0
Order By: Relevance
“…Here, the effect of immobilized surfactant-nanotube complexes on ES-mediated adhesion of tumor cells under flow was assessed. Sialylated carbohydrate ligands are expressed on the surface of many tumor cell types, which can induce rolling tumor cell adhesion on ES (47),(48) . We initially studied COLO 205 colon cancer cell and MCF7 breast cancer cell adhesion to ES on immobilized surfactant-nanotube surfaces, given that they have been shown to interact with ES under physiologically-relevant shear stresses (47),(49),(50) .…”
Section: Resultsmentioning
confidence: 99%
“…Here, the effect of immobilized surfactant-nanotube complexes on ES-mediated adhesion of tumor cells under flow was assessed. Sialylated carbohydrate ligands are expressed on the surface of many tumor cell types, which can induce rolling tumor cell adhesion on ES (47),(48) . We initially studied COLO 205 colon cancer cell and MCF7 breast cancer cell adhesion to ES on immobilized surfactant-nanotube surfaces, given that they have been shown to interact with ES under physiologically-relevant shear stresses (47),(49),(50) .…”
Section: Resultsmentioning
confidence: 99%
“…Using the parallel flow chamber assay, they confirmed the physiological role of CD24 as a ligand for P-selectin on KS cells in the presence of shear stress. 2 Later, Myung et al 115 reported the role of CD24 on MCF7 breast cancer cells as a ligand for E-selectin under flow by measuring the binding kinetics of CD24 with E-selectin with surface plasmon resonance (SPR). The identification of CD24 as a ligand for both P-and E-selectin may provide better understanding of the adhesion and invasion mechanisms of metastatic breast cancer.…”
Section: Metastatic Cascade: Adhesive Recruitment Of Cancer Cells Viamentioning
confidence: 99%
“…CD133 function is not clear but its presence on early and undifferentiated cells is suggestive of a growth factor receptor, and the presence of five tyrosine residues on the 50-aa cytoplasmic tail may indicate that the protein is phosphorylated in response to ligand binding and triggers a signal transduction [11]. CD24 is a sialoglycoprotein expressed on mature granulocytes [12], B and T lymphocyte subsets [13,14], normal and cancer stem cells [15,16]. The protein is anchored via a glycosyl phosphatidylinositol to cell surface.…”
Section: Discussionmentioning
confidence: 99%